Furthest ecology : poems - Fagin, Adam, 1979- (Mountain west poetry series., 2019)
"Furthest Ecology takes up the life and labor of Abbott Thayer, the prickly, irrepressible American painter and naturalist nicknamed "the father of camouflage." In 1896, Thayer discovered countershading, also known as "Thayer's Law," the theory of animal coloration often credited for laying the groundwork for military camouflage in World War I. Fagin's poetry follows Thayer through "pure leafy space" ringing with "hypertelic / rhythms of a redpoll," examining in lush, panoramic detail "the clairvoyance of the artist's attention." But this idyllic portrait unravels as Thayer's story proceeds. Grieving the death of his first wife and, later, cutting a frenzied path through wartime Europe, Thayer encounters darker forces, within and without. With spare beauty and sharp-edged syntax, Fagin conjures the painter's world: Loss, despair, obsession, ecstasy, and the aesthetic sublime. Furthest Ecology is a vivid and powerful debut that will haunt readers with its singular vision of artistic pursuit"--Provided by publisher.